Synthesis and structure of сopper(II) thiocyanate and nitrate complexes with 1-tert-butyl1H-1,2,4-triazolе - Degtyarik, Mikhail M.; Lyakhov, Alexander S.; Grigorieva, Inna M.; Ivashkevich, Ludmila S.; Grigoriev, Yuri V.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2022)
Complexes [Сu(NCS)2L3], [Сu(NO3)2L4] and [Cu(NCS)2L4]·L have been prepared by direct synthesis involving the interaction of metallic copper, ammonium salts NH4X (Х = NCS, NO3) and 1-tert-butyl-1H-1,2,4-triazole (L). Their composition and structure were determined by elemental analysis, single crystal X-ray analysis, and IR spectroscopy (range of 4000–500 cm–1). All the complexes showed mononuclear structure. In them triazole acts as a monodentate ligand, being coordinated by the N4 atom of the heterocycle. The NCS– and NO–3 anions display monodentate N- and O-coordination, accordingly. In [Сu(NCS)2L3], copper(II) cation has square-pyramidal environment of nitrogen atoms of two ligands L and two thiocyanate anions in the basal sites, and one nitrogen atom of ligand L in the apical position. In complexes [Сu(NO3)2L4] and [Cu(NCS)2L4]·L, copper(II) cations are octahedrally surrounded by nitrogen atoms of ligand L in the equatorial sites and by O or N atoms of corresponding anions in the axial positions.